Neuropsychotoxicity of Abused Drugs: Effects of Serotonin Receptor Ligands on Methamphetamine- and Cocaine-Induced Behavioral Sensitization in Mice - Yukio Ago; Shigeo Nakamura; Akemichi Baba; Toshio Matsuda (Elsevier, 2008)
Repeated administration of psychostimulants elicits a progressive enhancement of locomotor activity known as behavioral sensitization. Central dopamine (DA) neurons play key roles as the neural substrates mediating behavioral sensitization, but the role of the serotonin (5-HT) system in the sensitization is not fully elucidated. We have recently demonstrated that osemozotan, a specific 5-HT1A-receptor agonist, and ritanserin, a 5-HT2-receptor antagonist, inhibited the expression and development of both methamphetamine- and cocaine-induced behavioral sensitization in mice and that these drugs attenuated the maintenance of behavioral sensitization of methamphetamine, but not that of cocaine. We also found that azasetron, a 5-HT3-receptor antagonist, inhibited the expression and development of the sensitization induced by methamphetamine and cocaine, respectively. Neurochemical studies using a microdialysis technique showed that repeated methamphetamine enhanced the methamphetamine-induced increase in 5-HT release in the prefrontal cortex. The sensitization of 5-HT release in methamphetamine-treated mice was attenuated by osemozotan and ritanserin. These findings suggest that the 5-HT system plays an important role in methamphetamine- and cocaine-induced behavioral sensitization in mice and imply that 5-HT1A-receptor agonists and 5-HT2-receptor antagonists may have a potential therapeutic value for the treatment of methamphetamine abuse or psychosis. Keywords:: drugs of abuse, behavioral sensitization, methamphetamine, cocaine, serotonin (5-HT)-receptor ligand